Idiolek dan Gaya Bahasa Fiersa Besari di Youtube Atap Negeri - Fitriani, Dini Eka; Pertila, Dwi Marselina; Rahmawanti, Isna (Lingua Susastra, 2025)
This study aims to examine how Fiersa Besari's idiolect and language style in the Atap Negeri video series on YouTube shape his linguistic identity as a digital creator. Using a qualitative descriptive approach, data was obtained from three episodes of Atap Negeri (Southeast Sulawesi, Central Papua, and Central Kalimantan) through observation, transcription, and classification of narrative speech. From approximately 101 utterances, 13 idiolectal features and 38 stylistic features were identified and analyzed based on the theories of language variation, stylistics, and digital identity. The results of the study show four main idiolectal tendencies, namely the use of distinctive conjunctions (tapi, setelah, tatkala), local diction (seberes, kawan-kawan), classical diction (musabab, syahdan), as well as slang and emotional expressions (pake, baper, wahhh, alias) that form a poetic style of speech that remains familiar to Generation Z. In addition, the dominant language style includes personification, metaphor, hyperbole, cynicism, and repetition, which serve to reinforce Fiersa's persona as a reflective, humorous, and critical storyteller of social reality. These findings show that Fiersa's linguistic choices serve as a strategy for digital identity construction and language influence that has the potential to shape aesthetic language practices among young audiences. This study contributes to the study of digital sociolinguistics by showing how the idiolect and language style of content creators become symbolic capital in building persona and closeness with online communities.